Optimizing Tabarru' Funds in Sharia Insurance by Digital Donation-Based Crowdfunding - Diamantin Rohadatul Aisy (Research Synergy Foundation, 2021)
The COVID-19 pandemic had transformed people's lifestyles in various aspects, among which is the priority shift where health is the main priority in addition to basic needs. In addition, the mobility restrictions during the pandemic have made society adapts to digitalized activities. The phenomenon of increasing donations is also a new occurrence in the era of the COVID-19 pandemic, which shall be acknowledged as the digitized version of Indonesian tradition of mutual cooperation (gotong royong) to help each other to ease the burden on people affected by COVID-19. This phenomenon is similar to the concept of tabarru’’ funds in sharia insurance which uses the mutual assistance (ta'awun) principle among insurance participants. Due to the increase of public awareness of health and high solidarity in the midst of this pandemic, Islamic insurance can find opportunities to increase the number of Tabarru’' Funds participation, with a touch of digital innovation for wider reach in the society. This research aims to develop the management of sharia insurance combined with donation-based crowdfunding management to apply in optimizing tabarru’’ funds. This research was conducted using qualitative descriptive methods, to explore the qualitative datas in several phenomenon of sharia insurance and crowdfunding, and generate a description of the relationship between these phenomena. The results of this study explain that the crowdfunding management can be applied in management of tabarru' funds in Shria insurance, including the following (1) Prospective donors and prospective respondent are both can registered as insurance participants; (2) Donations paid by donors as insurance installment are collected in tabarru’ funds; (3) Every donors and respondents has the same rights over the donation funds; (4) Sharia insurance management applies the principle of crowdfunding transparency through the public financial statements of donation funds or tabarru’ funds, and the report of donor respondent’s progress.